2017
DOI: 10.1039/c6ta09602f
|View full text |Cite
|
Sign up to set email alerts
|

Self-oriented Sb2Se3 nanoneedle photocathodes for water splitting obtained by a simple spin-coating method

Abstract: Sb2Se3 nanoneedles for use as a photocathode for water splitting are fabricated by facile spin-coating. After sequential surface modification with n-TiO2 and Pt, a remarkable photocurrent of 2 mA cm−2 at 0 VRHE is realized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
92
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 97 publications
(103 citation statements)
references
References 41 publications
3
92
1
Order By: Relevance
“…The H 2 produced from the water was also monitored under similar operation conditions by gas chromatography (GC) as shown in Figure S12 (Supporting Information). [51] By comparing detected hydrogen gas with the expected amount obtained by the photocurrent, the faradaic efficiency (i.e., the ratio of the rate of H 2 evolution to that of e − /2) can be calculated.…”
Section: Resultsmentioning
confidence: 99%
“…The H 2 produced from the water was also monitored under similar operation conditions by gas chromatography (GC) as shown in Figure S12 (Supporting Information). [51] By comparing detected hydrogen gas with the expected amount obtained by the photocurrent, the faradaic efficiency (i.e., the ratio of the rate of H 2 evolution to that of e − /2) can be calculated.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been reported that Sb 2 Se 3 is intrinsically stable towards photocorrosion in strong acidic media unlike Cu 2 O, which is vulnerable to photocorroson 22 . Owing to these merits, the photocurrent density of the Sb 2 Se 3 photocathode has improved rapidly from the initially reported value of 2.5 mA cm −2 to 17.5 cm −2 at 0 V against the reversible hydrogen electrode (RHE) over the short period of its development [23][24][25][26] . However, it is still far below the theoretical maximum (about 40 mA cm −2 , assuming a 1.2 eV E g and a 100% incident photon-to-current efficiency (IPCE)).…”
mentioning
confidence: 99%
“…Cu 2 ZnSn(S,Se) 4 , [14] and Sb 2 Se 3 , [15] for which TiO 2 is mostly produced via atomic layer deposition (ALD), allowing for conformal deposition regardless of the surface morphologies. [18] Although TiO 2 protection improved the stability of photocathodes to some extent compared with their unprotected counterparts, a gradual photocurrent degradation was still unavoidable.…”
mentioning
confidence: 99%